2016
DOI: 10.1093/cz/zow022
|View full text |Cite
|
Sign up to set email alerts
|

Foraging ecology and occurrence of 7 sympatric babbler species (Timaliidae) in the lowland rainforest of Borneo and peninsular Malaysia

Abstract: Understanding foraging strategies of birds is essential to understanding mechanisms of their community assembly. To provide such information on a key Southeast Asian rainforest family, the babblers (Timaliidae), we evaluated foraging behavior and abundance in 7 morphologically and behaviorally similar sympatric species (Cyanoderma erythropterum, C. rufifrons, Stachyris maculata, S. nigricollis, S. poliocephala, Macronus ptilosus, and Mixornis gularis) in 5 habitats defined by structural complexity: (1) continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 84 publications
(106 reference statements)
1
17
0
Order By: Relevance
“…Morphology of understorey plants plays an important role in capturing the falling dead leaves. The understorey shrubs, woody vines [ 62 ], ferns, small palms [ 63 ], and rattans [ 64 ], which were abundant in the study area are very useful in intercepting the forest canopy litterfall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphology of understorey plants plays an important role in capturing the falling dead leaves. The understorey shrubs, woody vines [ 62 ], ferns, small palms [ 63 ], and rattans [ 64 ], which were abundant in the study area are very useful in intercepting the forest canopy litterfall.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by [ 64 ] showed that C . erythropterum exhibited somewhat similar foraging strategies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Our lack of detailed ecological knowledge of most species makes even hypothesizing likely networks of competitors difficult (Jankowski et al, 2012), beyond the relatively coarse metric of foraging guild or at the limited scale of genus. Diffuse competition may often result in niche differentiation based on foraging manoeuvres and strata rather than area occupancy, even among morphologically similar species with similar diets, as has been found for babblers (Timaliidae) in Malaysia (Mansor & Ramli, 2017;Styring, Ragai, Zakaria, & Sheldon, 2016). Competition may also be difficult to detect because elevational range overlap of strongly competing species may be effectively eliminated.…”
Section: Causes Of Occupancy Declines At Range Edgesmentioning
confidence: 99%
“…, Styring et al . ). In the Neotropics and Afro‐tropics, mixed‐species flocks of birds often forage at army‐ant swarm raids (Willis & Oniki , Peters et al .…”
mentioning
confidence: 97%
“…Multi-species foraging flocks are characteristic of tropical forest avian communities; these flocks are important subjects for analyzing the ecology of mixed-species assemblages (Powell 1979, Peron & Crochet 2009, Cordeiro et al 2015, Goodale et al 2015, Styring et al 2016). In the Neotropics and Afro-tropics, mixedspecies flocks of birds often forage at army-ant swarm raids (Willis & Oniki 1978, Peters et al 2008.…”
mentioning
confidence: 99%